Simple cobalt(II) chloride catalyzed N-alkylation of amines with alcohols - Midya, Siba P.; Mondal, Akash; Begum, Ayesha; Balaraman, Ekambaram (Synthesis-Stuttgart, 2017)
A facile cobalt-catalyzed N-alkylation of amines with alcohols using inexpensive, commercially available CoCl2 center dot 6H(2)O is reported. Employing this readily available cobalt catalyst, a variety of amines with wide functional group tolerance were selectively alkylated under benign conditions.
Keywords: (Hetero)Aromatic Amines; Alcohols; Amination; amines; Anilines; Aromatic-amines; Cobalt Catalysis; Dehydrogenation Borrowing Hydrogen; Efficient Catalysts; Hydrogen Autotransfer; Iridium; N-alkylation; Pincer-complex; Secondary Alcohols; Selective Alkylation

Manganese catalyzed N-alkylation of anilines with alcohols: ligand enabled selectivity - Landge, Vinod G.; Mondal, Akash; Kumar, Vinit; Nandakumar, Avanashiappn; Balaraman, Ekambaram (Organic and biomolecular chemistry, 2018)
Ligand enabled Earth-abundant manganese catalyzed N-alkylation of amines with alcohols via a hydrogen auto-transfer strategy is reported. The choice of the ligand plays a significant role in the alcohol reactivity (aliphatic or aromatic) toward N-alkylation reactions.

Manganese-catalyzed direct conversion of ester to amide with liberation of H 2 - Mondal, Akash; Subaramanian, Murugan; Avanashiappan, Nandakumar; Balaraman, Kambaram (Organic Letters, 2018)
A simple and efficient Mn-catalyzed acylation of amines is achieved using both acyl and alkoxy functions of unactivated esters with the liberation of molecular hydrogen as a sole byproduct. The present protocol provides an atom-economical and sustainable route for the synthesis of amides from esters by employing an earth-abundant manganese salt and inexpensive phosphine-free tridentate ligand.